Assessment for the sympathetic detonation characteristics of underwater shaped charge. Issue 5 (3rd September 2017) - Ko, Young-Hun; Kim, Seung-Jun; Yang, Hyung-Sik
Abstract: Understanding the sympathetic detonation of explosives is important from the standpoint of storage requirements and handling. Water has higher density than air, and hence, a shockwave propagates faster through water than through air. The main objective of this study is to measure the critical distance for the assessment of shock sensitivity of a shaped underwater charge. Explosive gap tests were performed to analyze the underwater sympathetic detonation of a shaped charge and the AUTODYN code was utilized to validate the shock sensitivity results for RDX explosives. To simulate sympathetic detonation, the Lee–Tarver reaction rate model of RDX was adopted, which was implemented in the AUTODYN material library. The shaped charge water gap model was simulated by the AUTODYN Euler mesh. The critical gap distance of the underwater shaped charge was quantitatively investigated.